2010
DOI: 10.1074/jbc.m109.047829
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the K+ Channel β-Subunit KCNE3 Reveals an Important Role in Intestinal and Tracheal Cl− Transport

Abstract: The KCNE3 ␤-subunit constitutively opens outwardly rectifying KCNQ1 (Kv7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
108
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 70 publications
(61 reference statements)
14
108
3
Order By: Relevance
“…In intestine (Fig. 1G-L), consistent with previous work, 21,22 KCNQ1 immunoreactivity was observed in basolateral membranes of crypt epithelial cells. Although we did not find colocalization of KCNQ1 and GLP-1 in intestinal villi, KCNQ1 was detected in the GLP-1 positive cell in intestinal crypt.…”
Section: Resultssupporting
confidence: 80%
“…In intestine (Fig. 1G-L), consistent with previous work, 21,22 KCNQ1 immunoreactivity was observed in basolateral membranes of crypt epithelial cells. Although we did not find colocalization of KCNQ1 and GLP-1 in intestinal villi, KCNQ1 was detected in the GLP-1 positive cell in intestinal crypt.…”
Section: Resultssupporting
confidence: 80%
“…The LCA results were surprising, since we saw no evidence of a change in net I sc and suggested that LCA was simultaneously activating an opposing current that nullified these changes in AM I sc . A likely mechanism would be an inhibition of basolateral cation conductances, and it is well established that the secretagogue action of cAMP and Ca 2ϩ involves the activation of distinct K ϩ channels (59,74). In T84 cells, Devor (20,22,33), Tabcharani (70,71), and Sheikh (68) demonstrated that the K ϩ channels involved in cAMP-and Ca 2ϩ -mediated secretion are different; cAMP action involves the KCNE3/ KCNQ1 channel, and Ca 2ϩ activates the KCNN4 and KC-NMA1 (MaxiK) channels.…”
Section: Discussionmentioning
confidence: 99%
“…The short form of KCNE3 protein that is expressed in mice migrates much more slowly (;37 kDa) in SDS-PAGE than would be predicted solely from its 103-residue length (;14 kDa), primarily because of glycosylation (3 sites) (5,14,38). Deglycosylation eliminates the 37-kDa band and leaves a single band for mouse KCNE3 at 14 kDa (38). The newly discovered portion of hKCNE3 does not contain additional consensus glycosylation sites (Fig.…”
Section: Experimental Validation Of Extended Hkcne3 and Hkcne4 Proteimentioning
confidence: 99%